Efektivitas Media Representasi Visual Rantai Makanan (V-Foodchain) Terhadap Peningkatan Hasil Belajar IPAS Materi Ekosistem Siswa Kelas IV Sekolah Dasar - Idris Firnandi; Muhammad Misbahudholam AR; Agus Wahdian (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine how visual representation media of the food chain, V-FoodChain, improved fourth-grade students’ ability to analyze ecosystems at SDN Paseraman 1 Arjasa, Sumenep Regency. This quantitative study used a pre-experimental design with a one-group pretest-posttest method. The research sample consisted of 10 students selected through total sampling. The research instrument was an essay test administered before and after the treatment. The data were analyzed descriptively and inferentially using a paired-sample t-test with SPSS. The results showed a significant improvement in students’ learning outcomes after the use of V-FoodChain media. The mean pretest score increased from 52.30 to 84.80 in the posttest, with a significance value of 0.000 (<0.05). The effect size was very large (d ≈ 2.2), indicating a strong practical effect. The standard deviation decreased from 16.82 to 10.27, showing more consistent learning outcomes among students. These findings indicate that V-FoodChain media is effective in improving IPAS learning outcomes on ecosystem material and supporting more consistent gains in elementary students’ abilities.